Social Enterprise as a Model to Improve Live Release and Euthanasia Rates in Animal Shelters - Thomsen, Jennifer; Thomsen, Bastian; Copeland, Kellen; Coose, Sarah; Blackwell, Sean; Dante, Vitoria (Frontiers in Veterinary Science, 2021)
This paper explored the role that social entrepreneurship may play in helping to improve euthanasia and live release rates in animal shelters. This paper used a qualitative, comparative ethnographic study that included semi-structured interviews, participant observation, and archival research. It compared two large animal shelters from the U.S. and Australia. Collectively, 21 formal interviews, more than 30 informal interviews, and participant observation were conducted over a 6-month time frame between the two countries. Findings indicate that three main factors may contribute to the transformation of non-profit animals shelters and result in improved euthanasia and live release rates, as well as animal caregiver burnout. These include: (1) professionalizing shelter management, (2) engaging with non-profit social enterprise activities, and (3) improving the efficiency of daily operations. In this paper, we argue that by embracing non-profit social enterprise activities, animal shelters may improve anthropocentric animal shelter activities to positively affect human and non-human rights, welfare, and agency. We do not contend that non-profit animal shelters should sacrifice their stated mission or ethics to include business practices. Rather, by professionalizing management and operations that include self-sustaining diverse revenue streams, it may free up time and resources to make a greater effect in positive non-human animal welfare and outcomes.